Associations Between Positive and Negative Affect and the Way People Perceive Their Health Goals - Plys, Ekaterina; Desrichard, Olivier (Frontiers in Psychology, 2020)
Objective Why are people who suffer from depressive symptoms or chronic negative mood less likely to adopt a healthy lifestyle? We postulated that adoption of health goals (HGs) and health behaviors is impeded by negative affect (NA) and facilitated by positive affect (PA). Our aim was to assess the associations between NA and PA, measured as a state and as a trait, and perceptions of HGs and related means. In our studies we tested the relationship between perceptions of HGs and affect measured as a state and as a trait. Methods Participants in three online studies were asked to choose and evaluate a health goal (Studies 1–3) or a health goal and related means (Study 3). In Study 1 we used the personal project analysis to assess 10 dimensions of HGs, inter-goal interference, and inter-goal facilitation; in Studies 2 and 3 we used a specially designed questionnaire to assess the difficulty, attainability, controllability, and congruency with self-identity of HGs and related means. We used the Positive and Negative Affect Schedule to measure trait and state affect and the NEO PI-R to measure neuroticism and extraversion. Results Participants perceived their HGs and related means in mood-congruent ways. High NA participants perceived their HGs to be less controllable, less attainable, more difficult, and less congruent with their self-identity. They also perceived their related means to be more difficult and less congruent with their self-identity. In contrast, high PA participants perceived their HGs and related means to be more attainable and more congruent with their self-identity, and they evaluated their related means as less difficult. In addition, our results suggest that state affect is better associated with perceptions of HGs than trait affect. Conclusion The adoption and attainment of HGs is likely to be facilitated by PA but impeded by NA. PA and NA may also impact the adoption and maintenance of healthy lifestyles. These results help provide a better understanding of the reasons why people with depression or negative mood adhere to behaviors that compromise their health.